Responsabilidad social universitaria e imagen institucional en la filial Requena de la Universidad Nacional de la Amazonía Peruana 2024 - Cenepo Paredes, Semira Graciela (2025)
The objective of this final report was to investigate the relationship between university social responsibility and institutional image at the Requena Branch of the National University of the Peruvian Amazon in 2024. A non-experimental applied research was carried out, with a sample of 236 students, using a questionnaire to collect information. The results indicated that university social responsibility is seen as regular (37%), as it occasionally provides opportunities for interaction with social sectors and offers courses on ethics and social responsibility. However, the university often includes students in research projects. In addition, it occasionally incorporates programs in its policies to promote ethical values and publishes an annual report on its environmental performance. Regarding the institutional image (35%) it is rated as regular, this is because, although they almost always have competent professional staff and perceive good quality in administrative services, sometimes they have close contact with other entities, a good landscape image and accessible admission processes. It was concluded that there is a significant relationship between the variables, evidenced by a coefficient of 0.464 and a bilateral significance of 0.000.